Growth Arrest Triggers Extra-Cell Cycle Regulatory Function in Neurons: Possible Involvement of p27kip1 in Membrane Trafficking as Well as Cytoskeletal Regulation - Kawauchi, Takeshi; Nabeshima, Yo-ichi (Frontiers in Cell and Developmental Biology, 2019)
Cell cycle regulation is essential for the development of multicellular organisms, but many cells in adulthood, including neurons, exit from cell cycle. Although cell cycle-related proteins are suppressed after cell cycle exit in general, recent studies have revealed that growth arrest triggers extra-cell cycle regulatory function (EXCERF) in some cell cycle proteins, such as p27(kip1), p57(kip2), anaphase-promoting complex/cyclosome (APC/C) and cyclin E. While p27 is known to control G1 length and cell cycle exit via inhibition of cyclin-dependent kinase (CDK) activities, p27 acquires additional cytoplasmic functions in growth-arrested neurons. Here, we introduce the EXCERFs of p27 in post-mitotic neurons, mainly focusing on its actin and microtubule regulatory functions. We also show that a small amount of p27 is associated with the Golgi apparatus positive for Rab6, p115 and GM130, but not endosomes positive for Rab5, Rab7, Rab8, Rab11, SNX6 or LAMTOR1. p27 is also colocalized with Dcx, a microtubule-associated protein. Based on these results, we discuss here the possible role of p27 in membrane trafficking and microtubule-dependent transport in post-mitotic cortical neurons. Collectively, we propose that growth arrest leads to two different fates in cell cycle proteins; either suppressing their expression or activating their EXCERFs. The latter group of proteins, including p27, play various roles in neuronal migration, morphological changes and axonal transport, whereas the re-activation of the former group of proteins in post-mitotic neurons primes for cell death.